Loss of the laminin subunit alpha-3 induces cell invasion and macrophage infiltration in cutaneous squamous cell carcinoma - Caley MP; Martins VL; Moore K; Lashari M; Nissinen L; Kahari VM; Alexander S; Jones E; Harwood CA; Jones J; Donaldson M; Marshall JF; et al. (Wiley, 2022)
Background Cutaneous squamous cell carcinoma (cSCC) is a common cancer that invades the dermis through the basement membrane. The role of the basement membrane in poorly differentiated cSCC is not well understood.Objectives To study the effect that loss of the laminin subunit alpha-3 (alpha 3) chain from the tumour microenvironment has on tumour invasion and inflammatory cell recruitment.Methods We examined the role of the basement membrane proteins laminin subunits alpha 3, beta 3 and gamma 2 in SCC invasion and inflammatory cell recruitment using immunohistochemistry, short hairpin RNA knockdown, RNA-Seq, mouse xenograft models and patient tumour samples.Results Analysis of SCC tumours and cell lines using antibodies specific to laminin chains alpha 3, beta 3 and gamma 2 identified a link between poorly differentiated SCC and reduced expression of laminin alpha 3 but not the other laminin subunits investigated. Knockdown of laminin alpha 3 increased tumour invasion both in vitro and in vivo. Western blot and immunohistochemical staining identified increased phosphorylated myosin light chain with loss of laminin alpha 3. Inhibition of ROCK (rho-associated protein kinase) but not Rac1 significantly reduced the invasive potential of laminin alpha 3 knockdown cells. Knockdown of laminin subunits alpha 3 and gamma 2 increased monocyte recruitment to the tumour microenvironment. However, only the loss of laminin alpha 3 correlated with increased tumour-associated macrophages both in xenografted tumours and in patient tumour samples.Conclusions These data provide evidence that loss of the laminin alpha 3 chain in cSCC has an effect on both the epithelial and immune components of cSCC, resulting in an aggressive tumour microenvironment.